PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP LOYALITAS KONSUMEN MELALUI KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA KONSUMEN CARICA MERK GEMILANG DI WONOSOBO - Elsa Amelia Putri; Ngatno Ngatno (Universitas Diponegoro, 2017)
This research is conducted by fast development in business world, that giving impact to the strategy of business competition among companies, one of the fastest growing industries is the typical souvenir industry in Wonosobo. Carica Gemilang as one of the industries engaged in the utilization of Carica fruit always provides the best in order to create customer satisfaction. However, Carica Gemilang has fluctuating sales, ups and downs each year especially on bottled carica products.The purpose of the research is to the determine the effect of price and product quality to consumer loyalty through consumer satisfaction at consumers Carica brand Gemilang in Wonosobo. The samples in this research were 100 respondents with accidental sampling technique. Data analysis method that been used is validity test, reliability test, correlation coefficient, coefficient of determination, simple and multiple regression analysis, significance test (T test and F test) using SPSS version 16.0 and Sobel Test with Preacher Tool.This research indicated that price and quality of products have a positive and significant influence to consumer satisfaction variables and consumer loyalty variables. Price variables that affect consumer loyalty through consumer satisfaction occurs full mediation, and product quality variables affecting consumer loyalty through consumer satisfaction occurs partial mediation (partial mediation).Based on the research, we can suggest that Carica Gemilang should providing discounts on purchases of certain amounts, improving product quality both in terms of taste and ability of product to last longer, paying more attention to customer satisfaction after making a purchase, and more innovative than its competitor’s product.